Dovište Dobre vode kod Foče / Holy Site of Dobre Vode near Foča - Duranović, Elvir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
In this is monographic paper the autor strives to show and clarify all aspects of the Dobre Vode Holy Site in the vicinity of Foča, starting from the introduction to the holy site's basic elements, through the presentation and analysis of folk tales about the holy site, to the presentation of the site's basic functions: healing, ritual and social ones. For the first time, in this paper the author made a statement about the pre-Islamic origin of this holy site which he tried to support with arguments.